IMPLEMENTATION OF THE 2025 PROJECT-BASED AND DIGITAL LITERACY CURRICULUM: OPPORTUNITIES, CHALLENGES, AND ITS IMPACT ONSTUDENT ADAPTABILITY IN THE GLOBAL ERA - Abdul Wahab Syakhrani (CV. ADIBA AISHA AMIRA, 2025)
The implementation of the 2025 project-based and digital literacy curriculum marks a major transformation in Indonesia's education system to address the challenges of globalisation and technological acceleration. This study aims to examine in depth the opportunities and challenges that arise in the implementation of this curriculum, as well as to analyse its impact on students' adaptability. Through the strengthening of project- based learning, students are encouraged to be active, collaborative, creative, and able to think critically in solving real-world problems. The integration of digital literacy enables students to access, understand, and utilise technology productively and ethically. However, the implementation process faces obstacles such as infrastructure gaps, limited teacher competencies, and cultural resistance to change. The study findings indicate that this curriculum has the potential to enhance students' adaptability, digital literacy, and character, although it still requires sustained support, intensive training, and strengthened collaboration among stakeholders. This research recommends synergy between schools, the government, and the community to ensure the success of curriculum reform and students' readiness to face the dynamic global era.